2006
DOI: 10.1007/s10495-006-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor-associated pro-apoptotic signaling in aged skeletal muscle

Abstract: Tumor necrosis factor-alpha (TNF-α) is elevated in the serum as a result of aging and it promotes pro-apoptotic signaling upon binding to the type I TNF receptor. It is not known if activation of this apoptotic pathway contributes to the well-documented age-associated decline in muscle mass (i.e. sarcopenia). We tested the hypothesis that skeletal muscles from aged rodents would exhibit elevations in markers involved in the extrinsic apoptotic pathway when compared to muscles from young adult rodents, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 63 publications
(110 reference statements)
3
71
0
1
Order By: Relevance
“…Thus IL-15 seems to function, at least in part, to inhibit apoptosis by blocking the signaling downstream of the TNFR. This is relevant in aging muscle because the extrinsic apoptotic pathway is very active in aged skeletal muscle (31). We speculate that the changes in IL-15 mRNA observed in the current study may represent an attempt to counter the pro-apoptotic environment typically observed in aged skeletal muscle.…”
Section: Discussionmentioning
confidence: 65%
“…Thus IL-15 seems to function, at least in part, to inhibit apoptosis by blocking the signaling downstream of the TNFR. This is relevant in aging muscle because the extrinsic apoptotic pathway is very active in aged skeletal muscle (31). We speculate that the changes in IL-15 mRNA observed in the current study may represent an attempt to counter the pro-apoptotic environment typically observed in aged skeletal muscle.…”
Section: Discussionmentioning
confidence: 65%
“…FBN rats. Caspase-8 and caspase-3 activity were both greater in aged skeletal muscles and aged muscles also had greater protein content of Fas-associated death domain protein (FADD) and BH3-interacting death domain agonist (Bid) [14]. However, increasing IL-15 systemically in a similarly aged group of rodents did attenuate the incidence of apoptosis in skeletal muscle.…”
Section: Interleukin-15 As An Apoptosis Inhibitormentioning
confidence: 97%
“…In particular, the death receptor-mediated pathway, triggered by TNF-α, is thought to play a significant role in age-related muscle loss [14,17,19,20], owing to its ability to promote muscle protein wasting [63,64] and myonuclear apoptosis [14,17,19,20,65]. Interestingly, the transduction of TNF- α signaling during aging may be fiber-type specific[14].…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 99%